Contemporary Canadian Art : A Selection of Work from the Canada Council Art Bank. - Ferguson, Bruce (East Hanover : Nabisco World Headquarters, 1980)
Bolduc, David ; Bowers, Robert ; Breeze, Claude ; Cameron, Alex ; Carr-Harris, Ian ; Champagne, Jean Serge ; Cicansky, Victor ; de Heusch, Lucio ; Ewen, Patterson ; Fafard, Joe ; Gagnon, Charles ; Gaucher, Yves ; Greer, John ; Iskowitz, Gershon ; Mackenzie, Robin ; Magor, Liz ; Murray, Robert ; N.E. Thing Co. ; Proch, Donald ; Snow, Michael ; Warkov, Esther ; Whittome, Irene ; Wieland, Joyce ; Wyse, Alex ; Young, Robert
Contemporary Canadian Art : A Selection of Work from the Canada Council Art Bank, Nabisco World Headquarters, East Haover, New Jersey, 1980
boek
Keywords: Canada